Peran Katalog Elektronik Untuk Meningkatkan Efisiensi dan Efektivitas Pengadaan Barang Atau Jasa di Badan Pendapatan Daerah Provinsi Jawa Timur - Ekaprasetia, Riyan Syah; Haryati, Eny (Soetomo Magister Ilmu Administrasi, 2025)
The rapid development of technology causes the government to utilize this technology to meet its needs. The East Java Provincial Government is implementing an online E-Purcashing System through the Electronic Catalogs. This program can help East Java Public Agencies to meet their needs and help empower MSMEs and Local Industry players. However, there are still obstacles in implementing this system, such as the system not yet being integrated in all districts/cities in East Java and technical problems with the system. The aim of the research is to analyze the effectiveness of the Procurement of Goods and Services at the Secretariat of the Regional Revenue Agency of East Java Province and to analyze the inhibiting and supporting factors in the process of Procurement of Goods and Services at the Secretariat of the Regional Revenue Agency of East Java Province. The research uses qualitative research. The research informants are the Budget User Authority (KPA), the Commitment Making Officer (PPK), the Treasurer, the third party for achieving domestic content (MSMEs being suppliers) and the supporting staff of the Commitment Making Officer. The focus of the research is to analyze the 8 dimensions of e-purchasing according to Presidential Regulation Number 12 of 2021 as well as the principles of Procurement of Goods/Services according to Presidential Regulation Number 16 of 2018. Data collection techniques are through interviews with data analysis through descriptive analysis. The results of the study prove that the effectiveness of the implementation of the E-Purchasing system is to produce the right goods/services from every money spent, increase the use of domestic products, increase the role of micro, small and cooperative businesses, increase the role of national business actors, support the implementation of research and utilization of goods/services from research results, increase the participation of the creative industry, realize economic equality and provide expansion of business opportunities and increase sustainable procurement that meets the principles of accountability and openness. For the inhibiting factors of the Procurement of Goods and Services process with Electronic Catalogs, some providers have not registered on the product showcase of certain electronic catalogs available and there are changes in policies that result in some policy programs needing to be reviewed. While the supporting factors are the existence of a good Communication process, the ability and skills of procurement resources that are team-oriented and accountable, strengthening Transparency and Accountability and Simplifying Procurement Procedures.